Analysis of the competitiveness of manufacturing small-format products using wide-format printing in comparison with other methods - Khmiliarchuk, O.; Bondaryna, V. (ТОВ «Видавництво Ліра-К», 2025)
The paper examines the reduction of the cost price of small-format products using wide-format digital printing by optimizing prepress preparation. The advantages and isadvantages of the technology under study are determined.
Keywords: optimizing; production